PENGARUH LIKUIDITAS, PERUSAHAAN AFILIASI, PERTUMBUHAN PENDAPATAN, DAN MANAJEMEN LABA TERHADAP BOOK TAX GAP PADA PERUSAHAAN NON FINANCIAL YANG TERDAFTAR DI BEI TAHUN 2011-2015 - Lola Apriyanti Raudhah; Muhammad Saleh (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this research is to examine the effect of liquidity, affiliated companies, revenue growth, and earning management toward the book tax gap of non financial which is registered in Indonesia Stock Exchange from 2011-2015. The research type used in this study is testing hypothesis, by using purposive sampling method and in which there are 42 target of sampling which become the investigated object. The data used in this study is secondary data obtained from the audited and anually financial statements for the fiscal year ended December 31, published by the reference center of the capital markets contained in the Indonesia Stock Exchange. The multiple regression analysis model is used to test thehypothesis. The results of this study indicate that (1) liquidity measured by quick ratio has impact on the book tax gap, (2) affiliated companies has no impact on book tax gap, (3)revenue growth has impact on the book tax gap, and (4) earning management has impact on the book tax gap.